DEGRADASI BOD DAN COD PADA SISTEM LUMPUR AKTIF PENGOLAHAN LIMBAH CAIR TEKSTIL - Wage Komarawidjaja (Jurnal Teknologi Lingkungan, 2007)
Observation of waste parameter in textile wastewater treatment wasdone. This experimental investigation consist of three mayor textileparameter including total suspended solid (TSS), biological oxygendemand (BOD) and chemical oxygen demand (COD). The parameterswere collected and analyzed. The TSS, BOD and COD consentration ineffluent of textile wastewater treatment is not exceeded the standard,but the efficiency of TSS, BOD and COD reduction is not statisticallysignificant.